Health workforce development planning in the Sultanate of Oman: a case study - Ghosh Basu (BMC, 2009)
Abstract Introduction Oman's recent experience in health workforce development may be viewed against the backdrop of the situation just three or four decades ago, when it had just a few physicians and nurses (mostly expatriate). All workforce categories in Oman have grown substantially over the last two decades. Increased self-reliance was achieved despite substantial growth in workforce stocks. Stocks of physicians and nurses grew significantly during 1985-2007. This development was the outcome of well-considered national policies and plans. This case outlines how Oman is continuing to turn around its excessive dependence on expatriate workforce through strategic workforce development planning. Case description The Sultanate's early development initiatives focused on building a strong health care infrastructure by importing workforce. However, the policy-makers stressed national workforce development for a sustainable future. Beginning with the formulation of a strategic health workforce development plan in 1991, the stage was set for adopting workforce planning as an essential strategy for sustainable health development and workforce self-reliance. Oman continued to develop its educational infrastructure, and began to produce as much workforce as possible, in order to meet health care demands and achieve workforce self-reliance. Other policy initiatives with a beneficial impact on Oman's workforce development scenario were: regionalization of nursing institutes, active collaboration with universities and overseas specialty boards, qualitative improvement of the education system, development of a strong continuing professional development system, efforts to improve workforce management, planned change management and needs-based micro/macro-level studies. Strong political will and bold policy initiatives, dedicated workforce planning and educational endeavours have all contributed to help Oman to develop its health workforce stocks and gain self-reliance. Discussion and evaluation Oman has successfully innovated workforce planning within a favorable policy environment. Its intensive and extensive workforce planning efforts, with the close involvement of policy-makers, educators and workforce managers, have ensured adequacy of suitable workforce in health institutions and its increased self-reliance in the health workforce. Conclusion Oman's experience in workforce planning and development presents an illustration of a country benefiting from successful application of workforce planning concepts and tools. Instead of being complacent about its achievements so far, every country needs to improve or sustain its planning efforts in this way, in order to circumvent the current workforce deficiencies and to further increase self-reliance and improve workforce efficiency and effectiveness.